Mangroves for Healthy Ecosystems and Resilient Economy: Sustainable Solutions Amidst Climate Change (KKN-PPM UGM 2024 JT-013 Wedung, Demak) - Wulandari, Cahyo; Marwadani, Laila Mei; Salsabila, Gesti Nola; Santoso, Azzam Rafif; Azis, Nur (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
The damage to the mangrove ecosystem in the coastal area of ​​Demak, Central Java, is increasingly worrying due to coastal abrasion, land conversion into ponds, and unsustainable human activities. The mangrove ecosystem as a green belt for coastal areas has an important role in maintaining environmental balance, preventing abrasion, providing habitat for various fauna, and providing economic benefits to the community. Seeing this urgency, a series of community service programs were carried out by UGM KKN-PPM Unit JT-013 2024 students to support mangrove conservation efforts, precisely in the Dukuh Tambak Seklenting area, Wedung Village, Wedung District, Demak Regency. The purpose of this program is to inventory the existing mangrove species, measure the ecological conditions of the mangrove ecosystem, create a mangrove distribution map, carry out mangrove rehabilitation through planting, and increase awareness and involvement of the local community in the sustainable use of mangrove resources. The methods used include literature studies, location surveys, interviews, field observations, real-time data collection, planting practices, socialization, and utilization practices. Based on the inventory data, five types of true mangroves and five types of associated mangroves were found. The mangrove species are dominated by fire-fire mangroves (Avicennia sp.), although mangrove species (Rhizophora sp.) are also commonly found. The results of ecological observations of the mangrove ecosystem indicate that the location conditions are suitable for mangrove growth with mangrove distribution mostly in riverbank areas. A total of one thousand mangrove propagules were successfully planted in planting activities involving collaboration between the community and representatives from each element of society. This community service program also includes sustainable utilization activities of mangrove vegetation. Several products that have been developed by the community, such as mangrove tea and coffee, have identified strategies and recommendations for production development with a blueprint. In addition, the manufacture of processed products in the form of mangrove soap was carried out to provide creative inspiration to improve the community’s economy. These programs have succeeded in increasing public awareness of the importance of mangrove conservation. The community participation-based approach has proven effective in supporting the preservation of the mangrove ecosystem. In addition, this program also supports the sustainability of the local economy through the wise use of mangrove resources.